La traducción al español de Pour un tombeau d’Anatole de Stéphane Mallarmé - Galán-Mañas, Anabel (2014)
In this article, I present some of the difficulties arising from the translation into Spanish of Pour un tombeau d’Anatole, by Stéphane Mallarmé. My aim is to break with the insignificance of translators, often considered as an emotionally empty being. Campaña has faced several difficulties during the translation of the unfinished elegy, such as the strategic decisions related to linguistic aspects. However, the main difficulty he had to deal with were the emotional issues involved in the translation of a literary text of deep psychological content. He also had to deal with the anguish and the pain that Mallarmé had impregnated in the elegy. As a result, the translation had left a deep trace in Campaña, who even stated that the translation of Pour un tombeau d’Anatole had been “the deepest spiritual experience in his life”.